1994
DOI: 10.1016/0014-5793(94)80197-5
|View full text |Cite
|
Sign up to set email alerts
|

Ion permeability induced in artificial membranes by the ATP/ADP antiporter

Abstract: The hypothesis on the additional function of the ATP/ADP antiporter (ANT) as uncoupling protein has been tested in proteoliposomes and planar bilayer phospholipid membranes (BLM). It is found that dissipation of the light-induced dpH in the dark is very much faster in ANT-bacteriorhodopsin proteoliposomes than in proteoliposomes containing bacteriorhodopsin as the only protein. Mersalyl treatment of ANT-bacteriorhodopsin proteoliposomes causes further increase in the dpH dissipation rate due to formation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 23 publications
(13 reference statements)
0
20
0
Order By: Relevance
“…Furthermore, a number of studies using electrophysiological techniques provide evidence for channel properties in carrier proteins, e.g. neurotransmitter transporters (Cammack and Schwartz, 1996;DeFelice and Blakely, 1996), the chloroplast triose phosphate carrier (Schwarz et al, 1994) as well as the mitochondrial ADP/ATP carrier (Tikhonova et al, 1994;Brustovetsky and Klingenberg, 1996). This concept is particularly attractive in view of the fact that conditions are known where large pores appear in the inner mitochondrial membrane (permeability transition pore, "megachannel") (Zoratti and Szabo, 1995;Bernardi and Petronilli, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a number of studies using electrophysiological techniques provide evidence for channel properties in carrier proteins, e.g. neurotransmitter transporters (Cammack and Schwartz, 1996;DeFelice and Blakely, 1996), the chloroplast triose phosphate carrier (Schwarz et al, 1994) as well as the mitochondrial ADP/ATP carrier (Tikhonova et al, 1994;Brustovetsky and Klingenberg, 1996). This concept is particularly attractive in view of the fact that conditions are known where large pores appear in the inner mitochondrial membrane (permeability transition pore, "megachannel") (Zoratti and Szabo, 1995;Bernardi and Petronilli, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a number of studies using electrophysiological techniques provide evidence for channel properties in carrier proteins, e.g. neurotransmitter transporters (Cammack & Schwartz, 1996;DeFelice & Blakely, 1996), the chloroplast triose phosphate carrier (Schwarz, Gross, Steinkamp & Flugge, 1994) as well as the mitochondrial ADP/ATP carrier (Tikhonova, Andreyev, Antonenko, Kaulen, Komrakov & Skulachev, 1994;Brustovetsky & Klingenberg, 1996).…”
Section: Elucidation Of the Mercurial-induced Uniport Modes On The Momentioning
confidence: 99%
“…ADP and bonkregic acid, or the immuno-suppressant drug cyclosporin A (CspA) [9 l l]. Recent publications have indicated that the PTP consists of either ANT alone [12,13], or a multi-protein complex consisting, in part, of hexokinase, porin and ANT [141.…”
Section: Introductionmentioning
confidence: 99%